ISSUES IN THE UNDERSTANDING OF MUHKAM AND MUTASHABIH PASSAGES OF THE QUR'AN - Ushama, Thameem (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
ISSUES IN THE UNDERSTANDING OF MUHKAM AND MUTASHABIH PASSAGES OF THE QUR'AN